Dorsolateral Flap for Volar Contractures - Ila Saha (Indian Journal of Plastic Surgery)
The dorsolateral flap from the same finger was used in 30 cases for resurfacing of the volar surface after release of contracture. It was observed that it is a versatile locap flap for resurfacing of finger defects.